Perbandingan Imunoekspresi p53 dan Caspase-3 Pada Mola Hidatidosa Parsial, Mola Hidatidosa Komplit, dan Koriokarsinoma - Reis, Odilia Dos; Agustina, Hasrayati; Hassan, Abdul Hadi; Hernowo, Bethy S (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2014)
ABSTRACT Background: Partial hydatidiform mole, complete hydatidiform mole and choriocarcinoma are gestational trophoblastic diseases which have high incidence in Indonesia. Most complete hydatidiform mole can transform into choriocarcinoma , but pathogenesis of the transformation  is remain unknown. Apoptosis plays an important role in the pathogenesis of human malignancy. p53 and caspase - 3 play a role in apotosis . The aim of this study is to evaluate the p53 and caspase-3  immunoexpression in partial hydatidiform mole, complete hydatidiform mole and choriocarcinoma Methods: This is an observational analytic cross  sectional  study, conducted on 30 cases of gestational trophoblastic diseases consisted of 10 cases of partial hydatidiform mole, 10 cases of complete hydatidiform mole and 10 cases of choriocarcinoma. Immunohistochemical  examination of p53 and Caspase-3 were  performed on all cases. Result : The result showed significant difference between the p53 immunoexpression in partial hydatidiform mole and choriocarcinoma (p = 0.002), there was no significant p53 immunoexpression difference between complete hydatidiform  mole and choriocarcinoma (p = 0.121), there was no caspase-3 immunoexpression difference between partial hydatidiform mole and choriocarcinoma (p = 0.160) and there was no caspase-3 immunoexpression difference between complete hydatidiform mole and choriocarcinoma  (p = 0.361). p53 Immunoexpresion was higher in the case of complete hydatidiform mole and choriocarcinoma but tend to be lower in partial hydatidiform mole. Conclusion : In conclusion, p53 may play a role in the pathogenesis of complete hydatidiform mole and choriocarcinoma, but has a lesser role in the pathogenesis of partial hydatidiform mole. Caspase-3 might not play a role in the pathogenesis of hydatidiform mole transformation into choriocarcinoma. Keywords: complete hydatidiform mole, partial hydatidiform mole, choriocarcinoma, p53, caspase-3.